Multidimensional Psychometrics of Teacher Educators' Professional Identity: An Initial Validation with Teacher Educators in Southeast Asia - Ryota Tsukawaki; Takayoshi Maki; Yoshitsugu Hirata; Kiichiro Okahana; Asami Shimoda; Aiko Tsushima; Mariko Omori (MDPI AG, 2023)
While prior quantitative research has proposed a scale for measuring teacher educators' professional identity in terms of two dimensions, a qualitative study and comprehensive review of the literature suggested that this factor actually consists of six dimensions: teacher of teachers, researcher, coach, curriculum developer, gatekeeper, and broker. The purpose of this study was to examine whether it is possible to measure teacher educators' professional identity in terms of these six dimensions. A total of 192 teacher educators from Southeast Asian countries (Cambodia, Vietnam, and Thailand) participated in this study and responded to items we developed to measure their professional identity in addition to providing their basic attributes such as age, gender, highest level of education, and years of service as teachers or teacher educators. The results of a confirmatory factor analysis indicated that the six-factor model was acceptable and permitted the assessment of teacher educators' professional identity in terms of six dimensions. The results also show that women exhibit a stronger professional identity as teachers of teachers than do men and that the higher the respondents' highest level of education, the stronger their professional identity as teachers of teachers, coaches, curriculum developers, or gatekeepers.